(untitled) (Commonwealth Journal of Local Governance, 2015)
The main objective of this paper is to examine the extent to which the capital city of Delhi has gained financial autonomy over the years. In order to better understand its progress, the paper compares the periods before and after the submission of the Third State Finance Commission Report of Delhi. The main findings suggest there have been some efforts to reduce reliance on transfers from upper tiers of government and to strengthen ‘own revenues’ atthe Municipal Corporation of Delhi (MCD). A greater diversification of tax and non-tax revenue sources is responsible for this improvement. In the second period, other tax sources such as corporation tax and electricity tax gained in importance. Non-tax revenues were also strengthened by higher collection of certain components such as conversion charges. However, own revenues have been inadequate to meet growing expenditure requirements, resulting in high revenue expenditure gaps. Further, the growth in Gross State Domestic Product (GSDP has not led to a rise in own revenues for MCD.Rather, the paper finds that higher GSDP and its tertiary sector components are associated with higher expenditures in MCD. As far as local revenues are concerned, higher GSDP is associated with higher transfers, but has no discernible impact on own revenues.